Mitochondrial dysfunction in pancreatic acinar cells: mechanisms and therapeutic strategies in acute pancreatitis - Chen, Fan; Xu, Kedong; Han, Yimin; Ding, Jiachun; Ren, Jiaqiang; Wang, Yaochun; Ma, Zhenhua; Cao, Fang (Frontiers in Immunology, 2024)
Acute pancreatitis (AP) is an inflammatory disease of the pancreas and a complex process involving multiple factors, with mitochondrial damage playing a crucial role. Mitochondrial dysfunction is now considered a key driver in the development of AP. This dysfunction often presents as increased oxidative stress, altered membrane potential and permeability, and mitochondrial DNA damage and mutations. Under stress conditions, mitochondrial dynamics and mitochondrial ROS production increase, leading to decreased mitochondrial membrane potential, imbalanced calcium homeostasis, and activation of the mitochondrial permeability transition pore. The release of mitochondrial DNA (mtDNA), recognized as damage-associated molecular patterns, can activate the cGAS-STING1 and NF-κB pathway and induce pro-inflammatory factor expression. Additionally, mtDNA can activate inflammasomes, leading to interleukin release and subsequent tissue damage and inflammation. This review summarizes the relationship between mitochondria and AP and explores mitochondrial protective strategies in the diagnosis and treatment of this disease. Future research on the treatment of acute pancreatitis can benefit from exploring promising avenues such as antioxidants, mitochondrial inhibitors, and new therapies that target mitochondrial dysfunction.